Pelaksanaan Hukum Pidana Dalam Konteks Pertanggungjawaban Pidana Untuk Pelaku Eksibisionisme - Namora, Mohammad Satria; Barraphindo Raseto; Muhammad Dirgantara Wibawa; Wahyu Adi Ramadhani; Liza Deshaini (Consensus : Jurnal Ilmu Hukum, 2025)
The phenomenon of exhibitionism in Indonesia is increasingly concerning because it can occur in various public spaces such as public transportation, highways, and even live broadcasts on social media. How is criminal law implemented in the context of criminal liability for perpetrators of exhibitionism? This research uses normative (normative juridical) research with a legislative and conceptual approach. In conclusion, exhibitionism is considered a criminal offense and is regulated by the Criminal Code and the Pornography Law. The Pornography Law (Law No. 44 of 2008) strengthens criminal sanctions against exhibitionism. Article 10 of the Pornography Law implicitly defines exhibitionism as displays of nudity or pornographic content in public places. Although the term "exhibitionism" is not always explicitly stated, this regulation confirms that Indonesian law criminalizes exhibitionism. Recommendation: There needs to be explicit regulation in the Criminal Code or a special law regarding exhibitionism as a criminal offense, as it is currently often interpreted as falling under the "morality" articles (e.g., Article 281 of the Criminal Code), the meaning of which can be vague or open to multiple interpretations. The aim is to facilitate law enforcement officials in establishing evidence and prosecuting.